2000
DOI: 10.1021/la991013x
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Atomic Force Microscopy Studies of the Escherichia coli Outer Membrane:  Structural Basis for Permeability

Abstract: The structural basis of the outer membrane permeability for the bacterium Escherichia coli is studied by atomic force microscopy (AFM) in conjunction with biochemical treatment and analysis. The surface of the bacterium is visualized with unprecedented detail at 50 and 5 Å lateral and vertical resolutions, respectively. The AFM images reveal that the outer membrane of native E. coli exhibits protrusions that correspond to patches of lipopolysaccharide (LPS) containing hundreds to thousands of LPS molecules. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
310
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(333 citation statements)
references
References 45 publications
20
310
2
1
Order By: Relevance
“…Such an increase in roughness has also been reported for E. coli 057 and the lytic phage A 157 phage-host system (Dubrovin et al, 2008). Further, AFM studies have shown that mechanical and chemical damage of cell surface results in increased roughness-including damage caused by EDTA (Amro et al, 2000), detergents (Camesano et al, 2000), proteases (F Malfatti, unpublished) (Camesano et al, 2000) and antibiotics (Braga and Ricci, 1998;Meincken et al, 2005). Marine phages lyse 10-50% of bacteria production in the upper ocean, and it would be interesting to observe if phage-infected bacteria and archaea could be identified through a surface 'signature'.…”
Section: Bacterial Surface and Morphologysupporting
confidence: 56%
“…Such an increase in roughness has also been reported for E. coli 057 and the lytic phage A 157 phage-host system (Dubrovin et al, 2008). Further, AFM studies have shown that mechanical and chemical damage of cell surface results in increased roughness-including damage caused by EDTA (Amro et al, 2000), detergents (Camesano et al, 2000), proteases (F Malfatti, unpublished) (Camesano et al, 2000) and antibiotics (Braga and Ricci, 1998;Meincken et al, 2005). Marine phages lyse 10-50% of bacteria production in the upper ocean, and it would be interesting to observe if phage-infected bacteria and archaea could be identified through a surface 'signature'.…”
Section: Bacterial Surface and Morphologysupporting
confidence: 56%
“…Similarly, Amro et al [35] suggested that depletion of the silver metal from the outer membrane may cause progressive release of lipopolysaccharide molecules and membrane proteins. This results in the formation of irregularly shaped pits and hence increases the membrane permeability.…”
Section: Colimentioning
confidence: 99%
“…It is well known that the outer membrane plays an essential role in providing a barrier of selective permeability for E. coli and other Gram-negative bacteria [23]. On the basis of the TEM investigation, after treatment with the catalysts, the cell wall and cell membrane would be destroyed, subsequently leading to a change in cell membrane permeability and leakage of intracellular substances.…”
Section: Bactericidal Activity Of Silver Loaded Alumina On E Colimentioning
confidence: 99%